Written notes and listening comprehension: A correlation study - Siegel, Joseph (Journal of Academic Writing, 2023)
Notetaking is a crucial aspect of learning in academic contexts, but as a relatively casual form of academic writing, it seldom receives pedagogic or research attention in the literature. Therefore, as more students study academic content through English as a second language (L2), research on student notetaking as a form of academic writing deserves attention. What students write in their notes and how they do so can play important roles in comprehension and learning. To address this gap, the present study examines 102 sets of notes and corresponding listening comprehension test scores to determine the relationships between four factors of quantity and quality in students’ hand-written notes; namely, notations, words, information units, and efficiency ratio. Results indicate that total notations and total words written in notes do not impact overall test scores, while information units and higher efficiency ratios positively correlate to test scores. The paper closes with pedagogic advice for teachers and students operating in L2 academic contexts with a focus on how best to conceptualise and write notes.